Differential Spatiotemporal Patterns of Galectin Expression are a Hallmark of Endotheliochorial Placentation - Conrad, Melanie L. (2016)
Problem: Galectins influence the progress of pregnancy by regulating key processes associated with embryo-maternal cross talk, including angiogenesis and placentation. Galectin family members exert multiple roles in the context of hemochorial and epitheliochorial placentation; however, the galectin prolife in endotheliochorial placenta remains to be investigated. Method of study: Here, we used immunohistochemistry to analyze galectin (gal)-1, gal-3 and gal-9 expression during early and late endotheliochorial placentation in two different species (dogs and cats). Results: We found that during early feline gestation, all three galectin members were more strongly expressed on trophoblast and maternal vessels compared to the decidua. This was accompanied by an overall decrease of gal-1, gal-3 and gal-9 expressions in late feline gestation. In canine early pregnancy, we observed that gal-1 and gal-9 were expressed strongly in cytotrophoblast (CTB) cells compared to gal-3, and no galectin expression was observed in syncytiotrophoblast (STB) cells. Progression of canine gestation was accompanied by increased gal-1 and gal-3 expressions on STB cells, whereas gal-9 expression remained similar in CTB and STB. Conclusion: These data suggest that both the maternal and fetal compartments are characterized by a spatiotemporal regulation of galectin expression during endotheliochorial placentation. This strongly suggests the involvement of the galectin family in important developmental processes during gestation including immunemodulation, trophoblast invasion and angiogenesis. A conserved functional role for galectins during mammalian placental development emerges from these studies.